Synthesis and structural of some α, β-unsaturated acetones containing 5-nitroarylfural - Anh, Nguyễn Thị Hiền; Triệu, Nguyễn Đình (Vietnam Journal of Chemistry, 2012)
Some derivatives of 5-nitro-2-furyl - arylvinyl ketones have been synthesized by condensed reaction of aryl methyl ketone with the heterocyclic aldehydes. Their structure was identified by IR, UV, 1H- NMR, 13C- NMR and mass spectra.